2018
DOI: 10.21037/jss.2018.06.16
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and revision rates following multilevel anterior cervical discectomy and fusion

Abstract: Background: Anterior cervical discectomy and fusion (ACDF) for cervical degenerative disease is an accepted treatment for symptomatic cervical radiculopathy and myelopathy. One-and two-level fusions are much more common and more widely studied. Outcomes and revision rates for three-and four-level ACDF have not been well described. The purpose of this study is to report on clinical outcomes and revision rates following multilevel ACDF. Methods: Patients who underwent three-or four-level anterior cervical discec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 13 publications
1
50
0
Order By: Relevance
“…It is routinely performed for one-and two-level cervical disc disease in patients presenting with cervical radicular symptoms or myelopathy. Surgical outcomes and symptom resolution are typically acceptable in patients undergoing one-and two-level ACDF [3]. For patients presenting with multi-level cervical disc disease, a three-to four-level ACDF may be necessary to address all levels involved.…”
mentioning
confidence: 99%
“…It is routinely performed for one-and two-level cervical disc disease in patients presenting with cervical radicular symptoms or myelopathy. Surgical outcomes and symptom resolution are typically acceptable in patients undergoing one-and two-level ACDF [3]. For patients presenting with multi-level cervical disc disease, a three-to four-level ACDF may be necessary to address all levels involved.…”
mentioning
confidence: 99%
“…In a recently published study, reductions of 26.1% in NDI, 33.4% in neck pain, and 50.4% in arm pain were reported for multilevel ACDF at 24 months. 38 However, multilevel ACDF may cause even greater stresses to adjacent discs, and, compared with single-level ACDF, multilevel ACDF yields higher rates of pseudarthrosis, complications, revisions, and reoperations. The 24month reoperation rate has been reported elsewhere to be 35% for patients who underwent 3-and 4-level cervical fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The 24month reoperation rate has been reported elsewhere to be 35% for patients who underwent 3-and 4-level cervical fusion. 38 In an effort to preserve segmental motion, both multilevel CDA and a hybrid surgical treatment combining CDA and ACDF have been considered. However, the preference of either of these motion-sparing treatments is dependent on the severity of disc degeneration and optimized patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that the definition of pseudoarthrosis varied significantly within the literature [22,23,24]. We stratified our patients with IF grade III for possible risk factors and could not identify any predisposing risk factors in our study (Table S2) [25,26,27].…”
Section: Discussionmentioning
confidence: 99%